Analisa OEE dan FMEA Untuk Menigkatkan Perfoma Mesin Sliter di PT PAS - Widyantoro, Murwan; Martono, Martono; Paduloh, Paduloh (universitas teuku umar, 2022)
PT. PAS is a company that produces noodles with the brand mie sedap. Based on the production data from the previous year, the noodle product activities carried out by PT. PAS, each month has not reached the target due to the time the damage occurred to the noodle slitter machine. So it is necessary to research to determine the performance of the noodle slitter machine using the OEE and FMEA methods. Based on the calculation results of the OEE value of the slitter machine is 76%, it can be concluded that the performance of the slitter machine is not ideal. Based on the analysis using FMEA, the cause of losses due to defect & rework losses is slitter syncing, and losses due to idling and minor stoppages are slitter shooting. The result of the implementation is that there is a significant increase in the OEE value after repairs to the slitter machine with an average OEE value of 91% so that the results of the improvements made by making automatic lubrication modifications can improve the performance of the slitter machine to ideal performance.Keywords— FMEA, OEE, Losses, Slitter